Efficient differentiation of human iPSC‐derived mesenchymal stem cells to chondroprogenitor cells1. Issue 2 (17th December 2012) - Guzzo, Rosa M.; Gibson, Jason; Xu, Ren‐He; Lee, Francis Y.; Drissi, Hicham
Abstract Induced pluripotent stem cells (iPSC) hold tremendous potential for personalized cell‐based repair strategies to treat musculoskeletal disorders. To establish human iPSCs as a potential source of viable chondroprogenitors for articular cartilage repair, we assessed the in vitro chondrogenic potential of the pluripotent population versus an iPSC‐derived mesenchymal‐like progenitor population. We found the direct plating of undifferentiated iPSCs into high‐density micromass cultures in the presence of BMP‐2 promoted chondrogenic differentiation, however these conditions resulted in a mixed population of cells resembling the phenotype of articular cartilage, transient cartilage, and fibrocartilage. The progenitor cells derived from human iPSCs exhibited immunophenotypic features of mesenchymal stem cells (MSCs) and developed along multiple mesenchymal lineages, including osteoblasts, adipocytes, and chondrocytes in vitro. The data indicate the derivation of a mesenchymal stem cell population from human iPSCs is necessary to limit culture heterogeneity as well as chondrocyte maturation in the differentiated progeny. Moreover, as compared to pellet culture differentiation, BMP‐2 treatment of iPSC‐derived MSC‐like (iPSC–MSC) micromass cultures resulted in a phenotype more typical of articular chondrocytes, characterized by the enrichment of cartilage‐specific type II collagen (Col2a1), decreased expression of type I collagen (Col1a1) as well as lack of chondrocyte hypertrophy. These studies represent a first step toward identifying the most suitable iPSC progeny for developing cell‐based approaches to repair joint cartilage damage. J. Cell. Biochem. 114: 480–490, 2013. © 2012 Wiley Periodicals, Inc.